2016
DOI: 10.1080/15548627.2015.1115172
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy is required for mitochondrial biogenesis and myogenic differentiation of C2C12 myoblasts

Abstract: Myogenesis is a crucial process governing skeletal muscle development and homeostasis. Differentiation of primitive myoblasts into mature myotubes requires a metabolic switch to support the increased energetic demand of contractile muscle. Skeletal myoblasts specifically shift from a highly glycolytic state to relying predominantly on oxidative phosphorylation (OXPHOS) upon differentiation. We have found that this phenomenon requires dramatic remodeling of the mitochondrial network involving both mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
325
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(362 citation statements)
references
References 22 publications
28
325
0
9
Order By: Relevance
“…This assumption is based on observations in myotube formation, showing dynamic remodeling of the mitochondrial network, including mitochondrial clearance and biogenesis [15]. Importantly, this mitochondrial remodeling is impaired when autophagy is inhibited [45]. In the human placenta, mitochondria of the syncytiotrophoblast show a different appearance, compared to cytotrophoblasts [4].…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is based on observations in myotube formation, showing dynamic remodeling of the mitochondrial network, including mitochondrial clearance and biogenesis [15]. Importantly, this mitochondrial remodeling is impaired when autophagy is inhibited [45]. In the human placenta, mitochondria of the syncytiotrophoblast show a different appearance, compared to cytotrophoblasts [4].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct role of mitophagy in erythrocyte maturation, mitophagy has been implicated in developmental transitions in muscle tissue. It was recently shown that, upon differentiation of mouse myoblasts, mitophagy is induced and is necessary for differentiation (Sin et al 2016). Furthermore, essential metabolic transitions that occur during differentiation of cardiomyocytes have been shown to be mitophagydependent (Gong et al 2015).…”
Section: Mitophagy During Development In Multicellular Organismsmentioning
confidence: 99%
“…While mitophagy can be induced artificially with respiratory chain inhibitors and uncoupling agents, such as carbonyl cyanide 3-chlorophenylhydrazone (CCCP) that depolarize mitochondria, it is also part of the response to key physiological stresses, such as hypoxia and nutrient deprivation [3]. In addition, mitophagy is a programmed component of developmental and differentiation processes, including elimination of paternal mitochondria from the fertilized egg [46] and removal of mitochondria during red blood cell production [7,8] and muscle differentiation [9]. By promoting elimination of dysfunctional, supernumery and/or aged mitochondria, mitophagy plays a central role in maintaining mitochondrial and cellular integrity.…”
Section: Introductionmentioning
confidence: 99%